SIGNIFICANCE OF MEASUREMENT OF LUNG OSMOTIC AND HAEMOSTATIC ARTERIOVENOUS GRADIENTS IN CHILDREN WITH VENTILATION-ASSOCIATED PNEUMONIA - A.V. Chuprova; M.Yu. Efimova; A.N. Shmakov; S.A. Loskutova ("Paediatrician" Publishers LLC, 2006)
The article demonstrated the data on changes of hemostasiologic and biochemical parameters measured in blood obtained from children with ventilationa associated pneumonia, from children with respiratory distress syndrome and from ventilated controls without pneumonia signs and symptoms. According to the results assessment, the changes of all measured lung biochemical and hemostasisaregulating parameters were severe in children who developed ventilationa associated pneumonia, and were changed to a lesser and minimal degrees in patients with RDS and controls, respectively. The mentioned changes were most evident in venous blood, clarifying the negative artertiovenous differences of the studied parameters in patients with pneumonia. The degree of arteriovenous differences of the studied parameters correlated with severity of ventilationa associated pneumonia and with the degree of pulmonary gas exchange impairment, thus allowing to consider these changes as early diagnostic criterion for ventilationa associated pneumonia in children. Key words: ventilation associated pneumonia, RDS, children, arteriovenous gradient, lung osmotic function, lung haemostatic function.